2023
DOI: 10.46690/ager.2023.03.02
|View full text |Cite
|
Sign up to set email alerts
|

Research on the differential tectonic-thermal evolution of Longmaxi shale in the southern Sichuan Basin

Abstract: The southern Sichuan Basin in China holds abundant shale gas resources; however, the shale gas bearing property shows great differences due to the multiple stages of tectonic transformation. The key to revealing the shale gas differential enrichment mechanism is to explore the thermal evolution characteristics during tectonic evolution. Therefore, taking the Luzhou and Changning blocks as an example, which have obvious differences in tectonic evolution, the organic geochemical conditions of Longmaxi shale were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…On the basis of the kerogen-type classification standard of TI, 38 the TI results show that the organic matter type of shale in the YC-LL1 well is type I, while that in the YC-LL2 well and YC-LL3 well is type I or type II 1 (Figure 9). Therefore, based on the comprehensive analysis of δ 13 C and TI, it could be speculated that the organic type of samples from the YC-LL1 well is type I with a higher hydrocarbon generation potential than II 1 , while that from the YC-LL2 well and YC-LL3 well is type I or type II 1 .…”
Section: Organic Matter Typementioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the kerogen-type classification standard of TI, 38 the TI results show that the organic matter type of shale in the YC-LL1 well is type I, while that in the YC-LL2 well and YC-LL3 well is type I or type II 1 (Figure 9). Therefore, based on the comprehensive analysis of δ 13 C and TI, it could be speculated that the organic type of samples from the YC-LL1 well is type I with a higher hydrocarbon generation potential than II 1 , while that from the YC-LL2 well and YC-LL3 well is type I or type II 1 .…”
Section: Organic Matter Typementioning
confidence: 99%
“…When shale is regarded as a hydrocarbon source rock, it can be demonstrated that the higher the organic matter content of hydrocarbon source rocks, the higher the natural gas content generated. , Therefore, when evaluating the hydrocarbon generation capacity of shale, that is, a kind of hydrocarbon source rock, the geochemical characteristics of the hydrocarbon source rock including organic matter abundance, organic matter type, and degree of organic matter evolution need to be involved . Switching to the perspective of being a hydrocarbon reservoir formation, with the successful exploitation of shale gas in North America, such as the Barnet, Marcellus, and Woodford shales, , shale gas in China also has received much attention from sedimentologists. Especially, the Wufeng–Longmaxi shale (i.e., from the upper Ordovician Wufeng to the lower Silurian Longmaxi formation) is currently the key stratum for commercial shale gas exploration and development in the whole Sichuan Basin and its periphery, represented by the southeast Sichuan Basin. , …”
Section: Introductionmentioning
confidence: 99%
“…With the vigorous development of unconventional reservoir exploration and development (Ozkan et al, 2009;Sayed et al, 2017;Dang et al, 2022;Zhao et al, 2023), horizontal well has been widely used for its effectively connecting with reservoirs and expanding oil production area (Joshi, 1991;Soliman and Boonen, 1996;Qun et al, 2022). Exploration and development practice has shown that fractures are key factors for deep gas development.…”
Section: Introductionmentioning
confidence: 99%
“…The rising demand of hydrocarbons as a clean and green energy source has caused the study of unconventional oil and gas resources. The unconventional mudrocks have received renewed research focus for over two decades because of their emergence as the source and reservoir for shale oil and shale gas (mudrocks include mudstones and shales). Major shale oil plays include the Shahejie, Kongdian, Qingshankou, Yanchang, Fengcheng, and Lucaogou shales in China ,, and the Bakken, Woodford, Eagle Ford formations in North America. Shale gas plays consist of the Wufeng-Longmaxi, Qiongzhusi, Shanxi-Taiyuan, and Yanchang shales in China and the Lewis, Antrim, New Albany, Ohio, Barnett, Marcellus, Haynesville, and Fayetteville formations in North America. , ,, …”
Section: Introductionmentioning
confidence: 99%